Quaternary semiconductor Ba8Zn4Ga2S15 featuring unique one-dimensional chains and exhibiting desirable yellow emission. Issue 55 (20th June 2019) - Li, Yan-Yan; Liu, Peng-Fei; Lin, Hua; Wu, Li-Ming; Wu, Xin-Tao; Zhu, Qi-Long
Abstract : Yellow emissive Ba8 Zn4 Ga2 S15, as the first example exhibiting a unique 1D chain structure in the quaternary X/Zn/Ga/Q system, was discovered. Abstract : The rational design and synthesis of low-dimensional chalcogenides with desired properties is vital but still an enormous challenge. Herein, a novel quaternary sulphide, Ba8 Zn4 Ga2 S15 (FJ-2 ), has been designed by a cation regulation strategy and successfully prepared. It comprises a one-dimensional (1D) {[Zn4 Ga2 S15 ] 16− }∞ anion chain constructed from supertetrahedron [Zn4 S10 ] clusters. The structure ofFJ-2 is unique, as in the literature there are no other 1D structures of the type X/Zn/Ga/Q (X = cations; Q = chalcogen). Moreover, FJ-2 exhibits strong yellow photoluminescence emission at room temperature. DFT calculations using the VASP software package have aided the understanding of the relationship between the optical properties and electronic structure.